Impact of mother’s own milk expression practices and processing treatments on infant health and growth outcomes: a systematic review protocol - Daniel Klotz; Carolyn Smith; Agnieszka Bzikowska-Jura; Marzia Giribaldi; Tanya Cassidy; Laura Cavallarin; Serena Gandino; Karolina Karcz; Chiara Peila; Bartłomiej Walczak; Aleksandra Wesolowska (BMJ Open)
Introduction Breastfeeding is the biological norm for infant nutrition. In certain scenarios, feeding at the breast is not possible, because of either maternal or neonatal reasons. In those cases, infants can still receive expressed mother’s own milk (MOM) and its beneficial properties. Mothers can express their milk using a variety of methods, while applying different hygiene practices, in different settings; moreover, expressed milk might receive processing before it is fed to the infant, particularly to reduce transmission of viruses such as cytomegalovirus to premature infants. The present protocol was designed to gather the evidence on the effect that the expression method, the hygiene regimen and setting and any processing used on expressed MOM can have on the clinical outcomes of recipient infants.Methods This systematic review will follow the methodological recommendations of the Cochrane Collaboration, in accordance with WHO recommendations and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We will apply a hybrid search strategy, by combining structured database search with predefined snowballing searches. We will include primary research studies only, without restrictions on the type and including observational studies; no publication time, setting or language restriction will be applied, provided the abstract is available in English. Studies evaluating different methods of MOM expression, hygiene practices or settings during expression, processing of MOM and reporting clinical outcomes on recipient infants will be eligible. The searches have been planned to be performed in April–May 2024. Two reviewers will independently perform the reference screening, data extraction and risk of bias analysis of eligible studies, by using standardised tools specific for each study design. Quantitative and thematic narrative data synthesis will be performed and statistical heterogeneity between studies tested. Meta-analyses of extracted data will be performed where applicable. For relevant outcomes, certainty of the evidence will be tested by using the Grading of Recommendations Assessment, Development and Evaluation approach.Ethics and dissemination Ethical approval is not required for this study since no original data will be collected. There is patient and public involvement throughout this research process. The results of this review will be disseminated through publication in a peer-reviewed journal and through conference presentations. Moreover, this systematic review will inform recommendations on milk banking of the WHO Department of Nutrition and Food Safety.PROSPERO registration number CRD42024523299.